Selling and Marketing of Franchising Rights in Finland - Karrus, Jaakko (My University, 2018)
Franchising was first introduced in the Finnish market in the 70’s and has since grown to between 250 and 300 active chains. Academic literature on selling and marketing of franchising rights in the Finnish market has not been updated in over a decade. The goal of this study was to produce up to date knowledge on the desired new franchisee profile formulation and selling and marketing efforts of chains operating in the Finnish market. The study group are members and candidate members of the Finnish franchising association Suomen Franchising-Yhdistys ry. Both, the chain management (franchisors) and the chain members (franchisees) are interviewed for this study. The first objective was to inquire and analyze the attributes and resources franchisors most desire on new franchisees and with what means of selling and marketing these entrepreneurs are discovered and brought in as members of the chain. The second objective was to measure, to which degree they are able to attain the attributes and resources they report to be looking for and to what degree each marketing channel performs in new franchisee recruiting. The study was carried out with a quantitative questionnaire survey. The study group gathered a total of 12 chain managers responsible of recruiting new franchisees to their chains and a total of 34 franchisees answers. Results of the study indicate that franchisors are specific on favoring a certain range of ages in new franchisees and some personality qualities such as willingness to work hard, perseverance and loyalty to franchisor were reported as the most desired qualities. The greatest shortcomings in desired attributes and realized attributes were loyalty to franchisor, financial level and local experience and networks of the franchisees. The traditional marketing channels conventions and print media are still well used and quite well received, but the digital platforms of publications and social media are rising to match, and among the younger end of franchisees to overtake, the traditional channels. Job advertisements are well performing activities in both print and digital channels and could be further benefitted by keyword -marketing and search engine optimization.
Keywords: franchising rights; Finnish market; franchisee profile; marketing channel; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|